The Marketing Mix Affecting the Perception of The Senior Foreigners in Tourism Service Quality: Andaman Area - Rajit Khongharn รจิต คงหาญ (Dusit Thani College Journal, 2018)
This research has a purpose of the study in the marketing Mix Affecting the perception of The Senior Foreigner in Tourism Service Quality: Andaman Area. The research objective is recognition in the quality of businesses in tourism industry by using conceptual framework i.e. the strategic conceptualization of the 7 P’s service marketing mix. This research data collection employs the survey method by 100 senior foreigner tourists who traveled in Andaman. The research analysis applies descriptive statistics method to discover frequency rate, percentage rate, average rate, standard deviation. Moreover, this research employs the analyzing inferential statistics method and multiple regression analysis method by the significance of statistics at 0.5. The results revealed that the man was 61-65 years as 55 percent who married as 37 percent and 32 percent of single and 31 percent of separated. The Senior Foreigner had the high level of the products desirability by average score of 3.88. Overall in the price was the middle level which had the average score of 3.39. In the promotion marketing desirability in overall was the middle range which had the average score of 3.29. In the personal was 3.65. Besides, the process was in the mid-level which had the average score of 3.33. The creation and presentation of the physical in overall was in the mid-level which had the average score of 3.27 and based on the analysis of the 7 P’s service marketing mix, the two primary impacts were discovered i.e. price and personnel which have the impact to the quality perceived value of elderly tourists in the Andaman Sea’s tourist attractions.